Research on the Construction of Evaluation System of College Physical Education Wushu Teaching under Multiple Intelligences Theory - Xuan Chen, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
In order to better improve the martial arts learning effect, this paper puts forward the design method of martial arts motion feedback system based on target intelligent tracking video processing. It optimizes the hardware configuration of the system, adds a composite tracker to the system, to effectively track the motion changes of different human targets, and further combines the real-time target intelligent tracking video processing technology. Build a moving target tracking model; then, based on the calculation of motion characteristic parameters, CRF method is used for motion behavior recognition and feedback. Measuring the data using smart PLS software and running different results included descriptive statistical analysis, correlation analysis, model fitness analysis, and the smart PLS Algorithm model also describes that graphical analysis related to the variables. It is the expectation of the Chinese Government to achieve urban-rural integration and close the urban-rural divide by lowering health inequities and enhancing social connections at the same time. Given that involvement in sports may provide a variety of physical and mental advantages, as a manner of increasing possibilities for social connections, community provision plays an important part in this regard. The overall results found that there is positive and significant relationships in-between